PNEUMATIC SYSTEM OPERATED BY COMPRESSED AIR (C.A.E): AIR-POWERED VEHICLE - VIN, LYE KEL (IRC, 2017)
Climate change and energy security require a reduction in travel demand, a modal shift, and technological innovation in the transport sector. Through a series of press releases and demonstrations, a car using energy stored in compressed air produced by a compressor has been suggested as an environmentally friendly vehicle of the future. Even under highly optimistic assumptions the compressed-air car is significantly less efficient than a battery electric vehicle. However, a pneumatic–combustion hybrid is technologically feasible, inexpensive and could eventually compete with hybrid electric vehicles. Especially when the world is hard pressed with the energy and fuel crisis, compounded by pollution of all kinds, any technology that brings out the solution in this problem is considered as a bounty. There are a number of main disadvantages of Petrol or Diesel-Powered Cars. First, oil is carbon based fuel and it will release greenhouse gases like CO2 when it is burnt. Secondly, drilling oil and transporting oil process are tedious as well as tremendously costly and it will be running out estimate in 50-150 years. Third, the global oil market price is not constantly stable and somehow the increasing on oil price will affect the living cost of people as well. In order to deal with, replacement for fuels driven car with new ones are possible. These particular problems has been ironed out and dealt with a new solution which is not only cost effective but also uses an effective method of installation by using Compressed Air Energy Storage pressure vessels. This concept uses air engine which powered by the expansion of externally supplied pressurized gas to perform work against a piston. This research paper describes of the most convenient and fitting materials selected, modelled through the SolidWorks software, run through Simulia Abaqus analysis and the composite material are tested for mechanical properties in lab.